2006
DOI: 10.1128/aem.72.5.3608-3614.2006
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(VI) Reduction by Anaeromyxobacter dehalogenans Strain 2CP-C

Abstract: Previous studies demonstrated growth of Anaeromyxobacter dehalogenans strain 2CP-C with acetate or hydrogen as the electron donor and Fe(III), nitrate, nitrite, fumarate, oxygen, or ortho-substituted halophenols as electron acceptors. In this study, we explored and characterized U(VI) reduction by strain 2CP-C. Cell suspensions of fumarate-grown 2CP-C cells reduced U(VI) to U(IV). More-detailed growth studies demonstrated that hydrogen was the required electron donor for U(VI) reduction and could not be replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 53 publications
5
100
0
Order By: Relevance
“…requires H 2 as an electron donor, which cannot be replaced by acetate (71). Thus, acetate and H 2 may serve as electron donors for U(VI) reduction by species of Geobacter and Amaeromyxobacter (55,71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…requires H 2 as an electron donor, which cannot be replaced by acetate (71). Thus, acetate and H 2 may serve as electron donors for U(VI) reduction by species of Geobacter and Amaeromyxobacter (55,71).…”
Section: Discussionmentioning
confidence: 99%
“…Various substrates (e.g., acetate, ethanol, glucose, and methanol) have been used either in the field or in microcosm studies, and most were capable of stimulating microbial U(VI) reduction (1,8,42,43,47,60); however, the addition of methanol did not always result in U(VI) reduction (49). Many microorganisms are known to reduce U(VI) in pure culture, including a hyperthermophilic archaeon (28), a thermophilic bacterium Thermoterrabacterium ferrireducens (29), the mesophilic dissimilatory metal-reducing bacteria Geobacter and Shewanella (67) and Anaeromyxobacter dehalogenans (71), the sulfate-reducing bacterium Desulfovibrio sp. (61), and fermentative bacteria such as Clostridium spp.…”
mentioning
confidence: 99%
“…These sequences were related to the known U(VI) reducer A. dehalogenans (45) and to a clone from a uranium mine sediment where uranium reduction was demonstrated (38).…”
Section: Microbial Communities (I) Major Trophic Groups Detectedmentioning
confidence: 99%
“…(Khijniak et al, 2005). Also, among this variety of U(VI)-reducing bacteria, a subset (e.g., Anaeromyxobacter dehalogenans (Wu et al, 2006), Geobacter metallireducens, Shewanella putrefaciens (Lovley et al, 1991) and Desulfotomaculum reducens (Tebo and Obraztsova, 1998)) have been reported to conserve energy from this reaction, and to couple it to growth.…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical mechanisms of microbial U(VI) reduction have been extensively studied for organisms belonging to the Desulfovibrio (Payne et al, 2004), Shewanella (BencheikhLatmani et al, 2005), Geobacter (Shelobolina et al, 2007) and Anaeromyxobacter (Wu et al, 2006) genera. However, these biochemical models may not apply to the whole spectrum of bacteria capable of this reaction, which comprises not only many other mesophilic Proteobacteria, but also Firmicutes e both sulfate-reducing and fermentative e e.g., Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%